DETECTION AND ITS CLINICAL VALUE OF MINIMAL RESIDUAL DISEASES IN ACUTE PROMYELOCYTIC LEUKEMIA - Jiang, Guo-sheng; Tang, Tian-hua; Bi, Ke-hong; Zhang, Yu-kun; Ren, Hai-quan; Zhao, Liang-yu; Guo, Gui-yue; Liu, Xiu-lan; Ren, Qing-hua; Jiang, Feng-qin; Liu, Chuan-fang; Peng, Jun; et al. (Chinese journal of cancer research, 2002)
Objective: To detect the minimal residual diseases (MRD) in acute promyelocytic leukemia (APL) after complete remission (CR) and to analyze its clinical value in prognosis. Methods: Reverse transcription Polymerase chain reaction (RT/PCR) was used to detect MRD of patients with APL. Results: MRD positive rate in patients with APL was 92.8% (39/42) before treatment and 56.7 (21/37) immediately after the ATRA or chemotherapy- induced CR. Furthermore, MRD positive rate wasrelated to the relapse in APL patients and could be considered as a marker to predict the relapse of patients with APL after CR. The MRD detection could also be applied to direct the consolidation therapy to prevent relapses. Conclusion: RT-PCR is valuable to monitor MRD and can be used as a marker to predict relapses.